The effect on jejunal mucosa of withdrawing and adding dietary gluten in cases of idiopathic steatorrhoea - Pollock, D. J. (1970)
Biopsy studies of the jejunal mucosa in patients with idiopathic steatorrhoea after periods on a gluten-free diet showed that the epithelium improved quickly in respect of surface cell height, mucosal thickness, and mitosis count, and more slowly in respect of villous height and width. In no case was recovery complete in every particular. Appearances seen through the dissecting microscope improved slowly and incompletely. Gluten loading after a period on a gluten-free diet partially reversed some of these mucosal changes in as short a time as five to seven days. Measuring such changes may help to hasten the diagnosis in some patients with suspected gluten-sensitive enteropathy in whom there is otherwise difficulty in assessing the clinical response to a gluten-free diet. The histological response of the jejunum to a gluten-free diet and to subsequent gluten loading may help to clarify the aetiological relationship between carcinoma and jejunal mucosal atrophy.